The Coordination of Fiscal and Monetary Policies in Pakistan: An Empirical Analysis 1980–2011 (The Pakistan Development Review, 2012)
Fiscal policy concerned with the government’s choice regarding the optimal use of taxation and government spending to control and adjust the aggregate demand in the economy. Monetary policy refers to the central bank’s control regarding the availability of credit in the economy to achieve the objective of price stability and this control can be exerted through money supply and interest rate channel. The ultimate objective of the both policies is to maximise the overall welfare of the society which can be achieved by keeping the inflation rate low and employment at its potential level. There are number of channels in which fiscal policy can impinge on monetary policy. An expansionary fiscal policy leads to an expansionary monetary policy, which may in turn fuel inflation and appreciate the domestic currency and that cause deterioration in the balance of payments. On the other hand if government finances the deficit through the markets (in a non-monetary way) then the fear of crowding out of the private sector arise in the economy. On external side when a country is depending on foreign funding of domestic debt, this results in deterioration in the exchange rate and balance of payment. Another more direct channel of fiscal policy is the impact of indirect taxes on price level. Besides this, perceptions and expectations of the general public about the large and on going budget deficits and resultant borrowings requirements may prompt a lack of confidence in the economic prospects. At the same time when people realise that government is borrowing for its own good, they will conclude that this can lead to higher taxation levels in future and consequently they consume less and save more, that is so called Recardian equivalence.